Negative Poisson's ratio for six‐constant tetragonal nano/microtubes. Issue 7 (15th May 2015) - Goldstein, Robert V.; Gorodtsov, Valentin A.; Lisovenko, Dmitry S.; Volkov, Mikhail A.
<x xml:space="preserve">Abstract</x> Analytical and numerical features of the elastic properties of curvilinearly anisotropic six‐constant tetragonal nano/microtubes are considered. The analytical formulas for Young's modulus and Poisson's ratio are obtained in the case of axial extension. Numerical calculations are performed using these formulas and data on the elastic constants from the Landolt–Börnstein Handbook. The parametric dependences of Young's modulus and Poisson's ratios for nano/microtubes are analyzed in detail. The basic parameters are elastic compliances, chiral angles, and ratios of the radii of hollow cylindrical tubes.